Exsolution intergrowth of cpx-opx and pseudosection modelling of two-pyroxene mafic granulite from Daltonganj of Chhotanagpur Granite Gneiss Complex, Eastern India - Kumar R.R.; Dwivedi S.B. (My University, 2025)
In this study, we reconstruct for the first time the evolution of a two-pyroxene mafic granulite from the Daltonganj of Chhotanagpur Granite Gneiss Complex (CGGC). Transmission electron microscopy (TEM) revealed that some of the clinopyroxene have exsolution texture, where orthopyroxene occurs as thin lamellae within the porphyroblast of clinopyroxene. To tightly constrain the P-T conditions at which exsolution lamellae developed after the metamorphic peak, we have applied both conventional and multi-equilibrium thermobarometry, as well as forward thermodynamic modelling. Results from multi-equilibrium thermobarometry, using the software THERMOCALC, suggest peak conditions of the mafic granulite at average pressure-temperature (PTav) conditions of 6.7 ± 1.19 kbar/814 ± 60 °C. In contrast, exsolution bearing opx-cpx minerals crystallised at relatively lower temperature (772 ± 14 °C), determined by the conventional geothermometers. The peak to retrograde evolution of these mafic granulites is constrained through phase equilibrium modelling in the NCKFMASHTO (Na2O–CaO–K2O–FeO–MgO–Al2O3–SiO2–H2O–TiO2–O) model system using the software Perple_X. Phase equilibria results of peak conditions (i.e. 6.0–6.78 kbar and 775–808 °C) are consistent with respect to those obtained through multi-equilibrium and conventional thermobarometry, while the retrograde path is defined down to ~4.5 kbar and ~540 °C. Our results have twofold implications: (i) they show how the integrating of different geothermobarometric methods is the best proxy to tightly constrain the evolution of high-grade metamorphic rocks, and (ii) they pavement to new constraints on the Paleoproterozoic to Neoproterozoic evolution of the CGGC. © 2021, Saudi Society for Geosciences.